2018
DOI: 10.1007/s00603-018-1579-x
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis of Slotting Operation Induced Failure Zones to Stimulate Low Permeability Coal Seams

Abstract: The main constrain for effective gas drainage in coal mines is the low permeability nature of coal reservoirs. As coal mining activities are extending to deeper subsurface, the ever-increasing in situ stress conditions is anticipated to result in much lower permeability and more challenges for gas emission control in coal mines. In recent years, hydraulic slotting using high-pressure waterjet along underground gas drainage boreholes, as a general solution to stimulate low permeability coal seams, has become in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 26 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…We use the strain‐softening Mohr‐Coulomb model to quantify the peak and the postpeak properties of the rocks. As being documented in many studies, this model is characterized by the cohesion and friction angle for peak strengths and by the alternation of both properties for the postpeak behavior. The difficulty of using this model lies in quantifying the relations between rock properties (cohesion and friction angle) and the accumulation of the plastic strains .…”
Section: Laboratory Tests and Development Of The Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the strain‐softening Mohr‐Coulomb model to quantify the peak and the postpeak properties of the rocks. As being documented in many studies, this model is characterized by the cohesion and friction angle for peak strengths and by the alternation of both properties for the postpeak behavior. The difficulty of using this model lies in quantifying the relations between rock properties (cohesion and friction angle) and the accumulation of the plastic strains .…”
Section: Laboratory Tests and Development Of The Numerical Modelmentioning
confidence: 99%
“…The difficulty of using this model lies in quantifying the relations between rock properties (cohesion and friction angle) and the accumulation of the plastic strains. 28,29 In this section, the following four steps were carried out to reveal the postpeak properties of rocks.…”
Section: Strengths Of the Rock Massesmentioning
confidence: 99%
“…Wei [31] simulated the formation of the stress relief area by hydraulic slotting utilizing PFC2D software and concluded that the effective slotting radius of the coal seam was 0.5 m and optimal hole spacing was 5 m. Lu et al [32] pointed out that, in the same seam, the optimal distance between the slots is 4 m. Zhang and Zou [33] and Cheng et al [34] established the prediction model of slotting depth and verified its precision in the field test. Si et al [35] discussed the influence of geological mechanical property, in situ stress, slotting shape, slotting spacing, and other key parameters on slotting performance. Lu et al [36,37] studied the influence of slotting parameters on fracture closure of soft and hard coal after slotting.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al established a theoretical constitutive model for damage of coal seam with hydraulic slotting. Si et al and Li et al have studied the variation of stress distribution around the borehole of hydraulic slotting borehole and determined the basic parameters of the hydraulic slotting. Zhang et al have analyzed the strain‐softening behavior of coal around hydraulic slotting borehole and the influence of coal failure on permeability.…”
Section: Introductionmentioning
confidence: 99%